1999
DOI: 10.1080/10301763.1999.10669200
|View full text |Cite
|
Sign up to set email alerts
|

Trade Union Amalgamations: Explaining the Recent Spate of Mergers in Australia

Abstract: This paper examines the determinants of amalgamation participation among Australian unions since the late 1980s. The analysis is based on data from the /996 Australian National Trade Union Survey. The results indicate that the Australian Council ofTrade Unions' amalgamation policy, declining membership and trade union officials have been central to participating in an amalgamation. The evidence also suggests that exclusive craft-based structures and union members have hindered the propensity of unions to engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…There is some literature that suggests such opposition forced changes upon the ACTU merger plan (Dabscheck 1995;Chaison 1996). The most comprehensive empirical study of union political factors found that mergers depended upon leadership from both the ACTU and the merger partners (Tomkins 1999). As for the membership, this study concluded 'the members have .…”
Section: Number Of Reduction In Number Ofmentioning
confidence: 81%
See 4 more Smart Citations
“…There is some literature that suggests such opposition forced changes upon the ACTU merger plan (Dabscheck 1995;Chaison 1996). The most comprehensive empirical study of union political factors found that mergers depended upon leadership from both the ACTU and the merger partners (Tomkins 1999). As for the membership, this study concluded 'the members have .…”
Section: Number Of Reduction In Number Ofmentioning
confidence: 81%
“…Tomkins' survey of union officers indicated that declining membership was a motive to merge, but confirmed little else from this list (Tomkins 1999). At best the impact of economic factors was felt only through the intermediate variable of membership decline.…”
Section: Number Of Reduction In Number Ofmentioning
confidence: 98%
See 3 more Smart Citations